Analisis Kesulitan Konsentrasi Belajar pada Siswa di Era Digital: Studi Kasus Berdasarkan Teori Gestalt - Agung Perdana; Mutiara Tanila; Yuliana Intan Lestari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The rapid advancement of digital technology has fundamentally transformed students’ learning environments, particularly in secondary education. While digital platforms offer extensive access to information, excessive exposure to digital stimuli often results in learning distractions that reduce concentration and depth of comprehension. This study aims to examine students’ learning concentration difficulties in the digital era using the perspective of Gestalt theory. Employing a qualitative case study approach, the research focuses on a junior high school student who experienced a decline in academic understanding associated with high levels of digital distraction. Data were collected through observation, in-depth interviews, and documentation, and analyzed using descriptive qualitative techniques. The findings reveal that digital distraction leads to fragmented information processing, preventing students from organizing learning materials into meaningful and coherent structures. From a Gestalt perspective, this condition inhibits insight learning, as students fail to perceive relationships among concepts as an integrated whole. The study underscores the importance of instructional strategies that promote holistic perception, such as visual organization, concept mapping, and attention management, to support effective learning in digital contexts. These findings confirm the continued relevance of Gestalt theory in explaining contemporary learning challenges and provide practical implications for educators in designing meaningful learning experiences in the digital era